Influence of perceptual and demographic factors on the likelihood of becoming social entrepreneurs in Saudi Arabia, Bahrain, and United Arab Emirates – an empirical analysis - Mir Shahid Satar; Ghadah Alarifi; Abdullah Abdulaziz Alkhoraif; Muzaffar Asad (Cogent Business & Management, 2023)
A growing body of literature contributes to empirical examination of social entrepreneurship (S-ENT) intention formation. However, the extant literature overlooks the influence of perceptual factors in explaining the individual's propensity to engage in S-ENT. Drawing on this gap and taking as starting point the literature on cognitive entrepreneurship, the study aims to identify and examine the influence of individual perceptual factors on the likelihood of becoming a social entrepreneur. A questionnaire survey was conducted to collect the data on adult population from three Gulf Cooperation Council (GCC) countries. The results of binomial logistic regression revealed the role of five individual perceptions (confidence in one's skills and knowledge, ability to perceive opportunities, knowing other social entrepreneurs, fear of failure, and perceived social passion) as influencing the likelihood of becoming a social entrepreneur. Additionally, the economic and demographic variables were also analyzed to reveal the significant differences. While addressing the shortcomings of previous studies, the results provided the groundwork for furthering research on S-ENT intentions and behavior in any similar context, thus providing the factors that need to be focused for enhancing the culture of S-ENT.
Keywords: 650; entrepreneurship behavior; perceptual variables; social entrepreneurs; social entrepreneurship; social passion